Saturday Night Fever: il soft body e la mascolinità passiva del nuovo divo-ballerino - Claudio Bisoni (Cinergie, 2016)
In this article, Saturday Night Fever (John Balham, 1977) is read as an example of a pop reappropriation of dance culture. It investigates the analogies and differences between the film and two other accounts of disco’s revolution: the article that inspired Saturday Night Fever (Tribal Rites of the New Saturday Night, by Nik Cohn) and the documentary The Secret Disco Revolution (Jamie Kastner, 2012). It furthermore analyses the types of dance depicted in the film, and the ways in which they connect to the mise-en-scène of Travolta/Manero’s body: a body which is represented as “soft”, and which on a narrative level uses dance to maintain an equilibrium between the active exercise of seduction and a particularly unusual form of abstinence.